(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2017)
Wittgenstein offers insights into the fluidity of relationships between ideas that we have of the world that appear to be immutable. These insights hint at problematics posed by mental health diagnoses that may fix ideas about the Being of a client in both client and therapist. The practice of existential phenomenology offers a method of unfixing the fixed.